2022
DOI: 10.3389/fmicb.2022.848057
|View full text |Cite
|
Sign up to set email alerts
|

Plants Dictate Root Microbial Composition in Hydroponics and Aquaponics

Abstract: The role of the microbial community in mediating fish and plant co-culture is often considered the black box of aquaponics. Despite widespread recognition regarding the dependency of plants on their rhizosphere, the extent to which upstream aquaculture influences downstream hydroponic root communities has been poorly described in the literature. In this study we performed a taxonomic survey (16S rRNA metabarcoding) of microbial communities originating in the facility water source, hydroponic nutrient solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…The present study revealed that the bacterial community in mature lettuce did not develop markedly from the RAS e uents. It has been shown in a soilless system that the plant played a more important role in determining the rhizosphere microbial community than the microbes in water (Lobanov et al 2022). Our results support the ndings of Lobanov et al (2022) as in our system the microbial communities in the lettuce were affected by the co-cultured plant species, but showed negligible transfer of bacteria from the RAS e uents to the lettuce.…”
Section: Microbial Communities and Sources In The Target Plant Lettucesupporting
confidence: 91%
“…The present study revealed that the bacterial community in mature lettuce did not develop markedly from the RAS e uents. It has been shown in a soilless system that the plant played a more important role in determining the rhizosphere microbial community than the microbes in water (Lobanov et al 2022). Our results support the ndings of Lobanov et al (2022) as in our system the microbial communities in the lettuce were affected by the co-cultured plant species, but showed negligible transfer of bacteria from the RAS e uents to the lettuce.…”
Section: Microbial Communities and Sources In The Target Plant Lettucesupporting
confidence: 91%
“…In our case, it is evident that WD proved to be an excellent solution for increasing the fresh weight of plants, but also the development and growth of the roots. Specifically, the root system plays a fundamental role in the growth of plants in hydroponics, which is even more important than in traditional soil growing [37]. Our results clearly show that the addition of WD to the nutrient solution showed a hormetic effect depending on the concentration used.…”
Section: Discussionmentioning
confidence: 63%
“…The microbiome diversity in soil and soilless tomato crops is likely to be different due to the different growing conditions and substrate types, as has been demonstrated by several authors [11,74,75], suggesting a facility-specific microbiome form within the rhizosphere for hydroponics systems, as well as other growing media [76,77]. Moreover, under soilless conditions, plant species can exert a stronger discriminatory influence on their rhizosphere composition [78]. Even the microbiology of the hydroponics rhizosphere and the substrate's effect remain understudied; to discuss our microbial community structure, we are going to mainly focus on soilless culture and/or tomato literature.…”
Section: Influence Of Recycled Fertilizers On the Bulk-substrate Micr...mentioning
confidence: 89%